2003
DOI: 10.1186/ar789
|View full text |Cite
|
Sign up to set email alerts
|

Higher susceptibility to Fas ligand induced apoptosis and altered modulation of cell death by tumor necrosis factor-α in periarticular tenocytes from patients with knee joint osteoarthritis

Abstract: ELISA = enzyme-linked immunosorbent assay; FACS = fluorescence activated cell sorting; FasL = Fas ligand; FCS = foetal calf serum; FITC = fluorescein isothiocyanate; OA = osteoarthritis; PCR = polymerase chain reaction; TNF = tumour necrosis factor; TNFRI = tumour necrosis factor receptor I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Bak (Bcl-2 homologous antagonist/killer) is a member of Bcl-2 gene family, but with a contrast function of promoting cell apoptosis [ 36 , 38 , 39 ]. Machner et al found that the expression of Fas mRNA in KOA patients was significantly higher than that in the control group by quantitative PCR [ 11 ]. Karaliotas et al reported a notable overexpression of median mRNA levels of BAX was also observed in patients with stage III KOA compared with the control, while the BCL2/BAX ratio was markedlydecreased [ 40 ].Płucienniket alfound that the BCL2/BAX ratiomay regulate the gene promoter methylation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bak (Bcl-2 homologous antagonist/killer) is a member of Bcl-2 gene family, but with a contrast function of promoting cell apoptosis [ 36 , 38 , 39 ]. Machner et al found that the expression of Fas mRNA in KOA patients was significantly higher than that in the control group by quantitative PCR [ 11 ]. Karaliotas et al reported a notable overexpression of median mRNA levels of BAX was also observed in patients with stage III KOA compared with the control, while the BCL2/BAX ratio was markedlydecreased [ 40 ].Płucienniket alfound that the BCL2/BAX ratiomay regulate the gene promoter methylation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-10 (IL-10) is a typical antiinflammatory Th2 cytokine which also includes IL-13 and IL-4, with IL-10 being the most potent amongst these [21] . In an IL-10 overexpression mouse model, researchers found some time-dependent effects on healing tendons [22] .…”
Section: Inflammatory Mediators and Immunocytes In Tendinopathymentioning
confidence: 99%
“…In an IL-10 overexpression mouse model, researchers found some time-dependent effects on healing tendons [22] . But the effects of IL-10 on tendon is still unknown [21] . Ricchetti et al delivered IL-10 into adult murine patellar tendon, and showed that the maximum stress of tendon was increased significantly in the IL-10 group [22] .…”
Section: Inflammatory Mediators and Immunocytes In Tendinopathymentioning
confidence: 99%
See 2 more Smart Citations